2020
DOI: 10.1016/j.acvd.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Renin-angiotensin system blockers and severe acute respiratory syndrome coronavirus 2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Some authors suggested switching from ACE inhibitors or ARBs with calcium channel blockers (CCBs), 4 although at the present time, the scientific community and French authorities recommend that patients continue their antihypertensive drug treatment unless they received contrary medical advice. 5 …”
mentioning
confidence: 99%
“…Some authors suggested switching from ACE inhibitors or ARBs with calcium channel blockers (CCBs), 4 although at the present time, the scientific community and French authorities recommend that patients continue their antihypertensive drug treatment unless they received contrary medical advice. 5 …”
mentioning
confidence: 99%